The Influence of the Creative Problem-Solving (CPS) Model on Students’ Learning Motivation and Mathematical Problem-Solving Ability - Anisa Risanda Damanik; Tanti Jumaisyaroh Siregar (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study tries to find out if using the Creative Problem Solving (CPS) model can improve the learning motivation and math problem-solving skills of eighth-grade students at MTs Akbar Insan Cendikia during the 2024/2025 school year. The study used a Quasi-Experiment method with a pre-test and post-test design that included both an experimental group and a control group. A total of 60 students were chosen through a purposive sampling method, with class VIII-A serving as the experimental group and VIII-B as the control group, each having 30 students. The tools used to collect data were a questionnaire to measure learning motivation and a test to assess problem-solving abilities. The data was analyzed using a t-test after checking for pretest scores, normality, and homogeneity. The results showed that the CPS model had a strong impact on increasing students' learning motivation, as the t-value obtained was 2.472, which is higher than the t-value from the table (2.002). It also had a significant effect on improving students' math problem-solving skills, with a t-value of 2.250, again higher than the t-value from the table (2.002). These findings show that the Creative Problem Solving model can be a good and effective method to enhance math learning in secondary schools.